Reviews in Fluorescence 2005 - Geddes, Chris D.; Lakowicz, Joseph R. (Reviews in Fluorescence,, 2005)
Reviews in Fluorescence 2005, the second volume of a new book serial from Springer, serves as a comprehensive collection of current trends and emerging hot topics in the field of fluorescence. It summarizes the year's progress in fluorescence, with authoritative analytical reviews specialized enough to be attractive to professional researchers, yet also appealing to the wider audience of scientists in related disciplines of fluorescence. Reviews in Fluorescence offers an essential reference material for any lab working in the fluorescence field. All academics, bench scientists, and industry professionals wishing to take advantage of the latest and greatest in the continuously emerging field of fluorescence will find it an invaluable resource. Key features: Comprehensive coverage of the year's hottest topics Chapters authored by known leading figures in the fluorescence field Accessible utility in a single volume reference New volume publishes annually Each Reviews in Fluorescence volume will be citable (ISI) and indexed Reviews in Fluorescence 2005 topics include: RNA folding and RNA-protein binding analyzed using fluorescence Progress in Lanthanides as luminescent probes The combined use of fluorescence spectroscopy and X-Ray crystallography to elucidating structure and dynamics of proteins Tapered fibers for cell studies Fluorescence-based ophthalmic glucose monitoring for diabetics High-throughput tissue image cytometry DNA condensation using FCS Multidimensional TCSPC About the Editors: Chris D. Geddes is Associate Professor, Director of the Institute of Fluorescence and Associate Director of the Center for Fluorescence Spectroscopy at the University of Maryland Biotechnology Institute, Medical Biotechnology Center, Baltimore. He has a B.Sc. from Lancaster University, UK and a Ph.D. in physical chemistry (fluorescence spectroscopy) from the University of Wales Swansea, UK. He is the Editor-in-chief of the Journal of Fluorescence, Who's Who in Fluorescence, and Reviews in Fluorescence as well as Executive Director of the Society of Fluorescence. Dr Geddes has published 100 scientific articles, papers, review articles and book chapters on the principles and applications of fluorescence. Joseph R. Lakowicz is Professor of Biochemistry at the University of Maryland School of Medicine, Baltimore and Director of the Center for Fluorescence Spectroscopy. Dr. Lakowicz has published over 400 scientific articles, has edited numerous books, holds 16 issued patents, and is the sole author of the widely used text, Principles of Fluorescence Spectroscopy, published by Kluwer Academic/Plenum Publishers, now in its 2nd Edition.